2001
DOI: 10.4319/lo.2001.46.5.1171
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial recolonization of deposit‐feeder egesta: In situ regrowth or immigration?

Abstract: The related processes of disturbance, recolonization, and succession can play major roles in structuring communities and in generating spatial heterogeneity. Nonequilibrium processes have been little studied with respect to microbial community dynamics. Here we report experimental efforts to identify the mechanisms of recolonization of egesta employing two intertidal deposit feeders, Balanoglossus aurantiacus and Nereis succinea. Using direct microscopic counts and Biolog plates, we compared the quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
3
16
1
Order By: Relevance
“…The presence of bacteria in fecal materials produced by copepods feeding on axenic food also confirmed that enteric bacteria can be passed onto fecal pellets (Tang 2005). On the other hand, a study with deposit-feeders showed that bacterial proliferation on egesta was faster than could be explained by growth alone (Plante & Wilde 2001), indicating that colonization by external bacteria must have also occurred at the same time.…”
Section: Zooplankton Fecesmentioning
confidence: 68%
“…The presence of bacteria in fecal materials produced by copepods feeding on axenic food also confirmed that enteric bacteria can be passed onto fecal pellets (Tang 2005). On the other hand, a study with deposit-feeders showed that bacterial proliferation on egesta was faster than could be explained by growth alone (Plante & Wilde 2001), indicating that colonization by external bacteria must have also occurred at the same time.…”
Section: Zooplankton Fecesmentioning
confidence: 68%
“…While microbial processing of whole-leaf litter would also involve the same general changes, only a modest decline in C/N ratio was noted for the litter bag experiment even after >110 d for both Avicennia marina and Rhizophora stylosa leaf litter. Significant microbial colonisation often results from addition of 'seed' bacteria from the gut of deposit-feeders or those present in the environment, or through regrowth of bacteria surviving through the digestive process (Plante et al 1989, Plante & Wilde 2001. Loss of feeding deterrents, such as phenolics, and dissolved organic matter, by leaching, a predominantly physical process, is also expected to be increased.…”
Section: Shredded Leaf Litter -Alternative Form Of Mangrove Export?mentioning
confidence: 99%
“…These biological activities have an enormous impact, not only on the reworking of the sediment, but also on the abundance and community structure of microorganisms in the sediment (Dobbs and Guckert, 1988;Steward et al, 1996;Marinelli et al, 2002;Lucas et al, 2003;Papaspyrou et al, 2006). Microbial abundance tends to increase along the inner walls of the burrows (Alongi, 1985;Aller and Aller, 1986;Lucas et al, 2003;Wu et al, 2003;Wada et al, 2006) and around the feces excreted from the animals (Hargrave, 1976;Plante and Wilde, 2001). Various bacteria actively facilitate the decomposition of the organic matter at these sites (Aller et al, 1983;Reichardt, 1988).…”
Section: Introductionmentioning
confidence: 99%